Economic efficiency of cultivation of agricultural crops on green mass - O. A. Blagopoluchnaya; N. I. Devterova (Новые технологии)
The purpose of the scientific work was to assess the economic efficiency of cultivating red clover and mixed soybean and corn crops for green mass, depending on the use of increasing doses of nitrogen fertilizers. The research was carried out in the fields of the Adyghe Research Institute of Agriculture, the soil of which is represented by heavy in mechanical composition merged chernozem. The content of physical clay throughout the profile is quite high – up to 78%. Tillage was applied with a plow PN-4-35 to a depth of 25–27 cm. It was revealed that the average yield of mixed crops of corn and soybeans for three years of research on the entire experimental site was 35,14 t/ha, perennial legumes for two years of research 18,67 t/ha. The yield of the green mass of soy and corn forage mixture, red clover is higher in all indicators on the variant with the introduction of the highest dose of nitrogen. The yield increases obtained depending on the use of increasing doses of nitrogen have been statistically proven (corn-soy mixture NSR05 ~ +3,5 t/ha), (clover NSR05 ~ +1,25 t/ha). Analysis of calculations of economic efficiency of cultivation of mixed crops of corn and soybeans showed that in all variants the level of profitability of products amounted to 91,1–117,7%. The income from the sale of products varied in the range of 14 469,6–21 169,7 thousand rubles/ha. The minimum income from the sale of the green mass of corn-soy mixture in the control variant is 14 469,6 thousand rubles/ha, the maximum in the variant with the highest dose of top dressing is 21 169,7 thousand rubles/ha. With a yield of red clover of 20,1 t/ha, the conditional net income from 1 hectare amounted to 3 963,0 rubles, the profitability level is 24,6%. Thus, the cultivation of corn-soy mixture and red clover by all economic indicators is possible without loss for an agricultural enterprise and it is advisable to include a raw material conveyor in the system.